Novel amide derivatives containing an imidazo[1,2-a]pyridine moiety: Design, synthesis as potential nematicidal and antibacterial agents - Wei, Chengqian; Huang, Junjie; Luo, Yuqin; Wang, Shaobo; Wu, Sikai; Xing, Zhifu; Chen, Jixiang (Pesticide biochemistry and physiology, 2021)
To discover new nematicides, a series of novel amide derivatives containing an imidazo[1,2-a]pyridine moeity were designed and synthesized. Among the title compounds, compounds 3 and 27 exhibited good nematicidal activities against Aphelenchoides besseyi (rice white-tip nematode), with LC50 values against of 27.3 and 35.9 mg/L, respectively, which were superior to that of fosthiazate (45.4 mg/L). Meanwhile, the LC50 value of compound 27 against Caenorhabditis elegans was 5.7 mg/L, which was superior to that of fosthiazate (77.2 mg/L). Compound 27 not only binds well to acetylcholinesterase (AChE) of nematodes, but also has a good inhibitory activity against AChE. Thus, AChE may be a potential target of compound 27 against nematodes. Unexpectedly, compound 28 exhibited excellent antibacterial activities with EC50 values of 1.2 and 3.1 mg/L against Xanthomonas oryzae pv. oryzae (Xoo) and Xanthomonas oryzae pv. oryzicola (Xoc), respectively, which were superior to those of bismerthiazol (68.6 and 77.1 mg/L) and thiodiazole copper (80.8 and 96.6 mg/L). The curative and protective activities of compound 28 against bacterial leaf blight were 37.0% and 36.8% at 50 mg/L, respectively, which were higher than those of thiodiazole copper (16.1% and 15.5%). In addition, compound 28 may inhibit the growth of Xoo by affecting the production of cell membranes and extracellular polysaccharides. Amide derivatives containing an imidazo[1,2-a]pyridine moeity can be used as good lead–structures to discover new nematicidal and antibacterial agents in the future. [Display omitted] •Twenty-eight novel amide derivatives containing an imidazo[1,2-a]pyridine were designed and synthesized.•Compound 27 exhibited good nematicidal activities against A. besseyi and C. elegans.•The AChE might be a potential target of compound 27 against nematodes.•Compound 28 exhibited excellent bactericidal activities against Xoo and Xoc.